Transcriptional landscapes underlying Notch-induced lineage conversion and plasticity of mammary basal cells - Merle, Candice; Rodrigues, Calvin; Langeroudi, Atefeh Pourkhalili; Journot, Robin; Rost, Fabian; Dang, Yiteng; Rulands, Steffen; Fre, Silvia (bioRxiv, 2024)
The mammary epithelium derives from multipotent mammary stem cells (MaSCs) that progressively restrict their potency and engage into lineage commitment during embryonic development. Although postnatal mammary progenitors are lineage-restricted and unipotent, several lines of evidence have documented their extensive plasticity and ability to reactivate multipotency in several non-physiological contexts. We have previously shown that ectopic Notch1 activation in committed mammary basal cells, which never experience Notch activity in homeostatic conditions, triggers a progressive cell fate switch from basal to luminal cell identity in both the pubertal and adult mouse mammary gland. Here, we tested the conservation of this mechanism in other glandular epithelia and found that constitutive Notch1 signaling also induces a basal-to-luminal cell fate switch in adult cells of the lacrimal gland, the salivary gland, and the prostate. Since cells do not undergo lineage transition synchronously and this switch is progressive in time, we performed single cell transcriptomic analysis by SMART-Seq on index-sorted mutant mammary cells at different stages of lineage conversion, to reveal the molecular pathways underlying the fate transition. Combining single cell transcriptomics analyses with assays in organoid cultures, we demonstrate that proliferation of basal mutant cells is indispensable to convert them into luminal progenitors. We thus reveal the molecular mechanisms and individual transcriptional landscapes controlling lineage conversion and cellular plasticity of unipotent committed mammary cells in vivo with spatial and temporal resolution. Given the strong implications of Notch signaling in cancer, these results also provide important insights into the mechanisms that drive cellular transformation.